2015
DOI: 10.1111/apt.13315
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐free regimens for chronic hepatitis C overcome the effects of portal hypertension on virological responses

Abstract: SUMMARY BackgroundPortal hypertension is the strongest predictor of virological response to pegylated interferon (IFN)/ribavirin in patients with chronic hepatitis C (CHC)-related cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 46 publications
3
29
1
Order By: Relevance
“…Eight patients (24%) had a >20% fall in HVPG, in 4 of whom it dropped to a value of <12 mm Hg. 63 Mandorfer et al 69 studied 56 patients with cirrhosis in whom HVPG was measured before starting treatment with SOF with RBV or DCV or SMV (simeprevir) for 12-24 weeks. Forty-one (73%) of these patients had a baseline HVPG >10 mm Hg.…”
Section: Decompensated Cirrhosismentioning
confidence: 99%
“…Eight patients (24%) had a >20% fall in HVPG, in 4 of whom it dropped to a value of <12 mm Hg. 63 Mandorfer et al 69 studied 56 patients with cirrhosis in whom HVPG was measured before starting treatment with SOF with RBV or DCV or SMV (simeprevir) for 12-24 weeks. Forty-one (73%) of these patients had a baseline HVPG >10 mm Hg.…”
Section: Decompensated Cirrhosismentioning
confidence: 99%
“…In our study involving 80 patients with advanced liver cirrhosis, we described an overall improvement of parameters associated with liver synthesis in the far majority of patients already during therapy while platelet counts showed different (delayed) kinetics of improvement. 2 Together with the preliminary findings by Karlas et al, and the Austrian experience recently present in this journal, 3 we would propose that future studies need to address the following issues:(i) what is relative contribution of inflammation vs. fibrotic scarving to portal hypertension? (ii) what will be the longterm kinetics of liver function parameters and liver stiffness values after HCV clearance?…”
mentioning
confidence: 83%
“…The study showed that 24% of these patients had a fall in HVPG to the extent exceeding 20%, and in half of them the HVPG had dropped to a value of <12 mmHg. The second study 60 enrolled 56 patients with cirrhosis in whom HVPG was measured before starting treatment with SOF + RBV or DCV and simeprevir (SMV) for 12-24 weeks. Majority (73%) of these patients had a baseline HVPG >10 mm of Hg.…”
Section: Improvement In Portal Hypertensionmentioning
confidence: 99%